Retention of Freshness in Fig Fruit by CO2-Enriched Atmosphere Treatment or Modified Atmosphere Packaging under Ambient Temperature - Mathooko, Francis M.; Sotokawa, Tetsuo; Kubol, Yasutaka; Inaba, Akitsugu; Nakamura, Reinosuke (THE JAPANESE SOCIETY FOR HORTICULTURAL SCIENCE, 1993)
At 20•C, freshness retention of figs (Ficus carica L. cv. Masui Dauphine) by CO2-enriched atmosphere treatment or modified atmosphere packaging were studied in an attempt to reduce deterioration during transportation. CO2-enriched atmosphere treatment inhibited ethylene production, delayed the incidence of mold growth and promoted ethanol production. Majority of the figs exposed to 60% or 80% CO2 for 2 days were still marketable 1 day after transfer to air at 20•Ž. Based on mold growth, figs stored in air and in unperforated polyethylene bags deteriorated slightly faster than those stored in perforated bags. A gas mixture of 80% CO2 +20% O2 or 100% CO2 introduced into the polyethylene bags before sealing were more effective in the control of mold growth compared to air or 100% N2 and equally effective in reducing ethylene accumulation as 100% N2. The results suggest that postharvest deterioration of figs can be reduced by